Ринок міжнародних автомобільних перевезень вантажів України в умовах інтеграції до єдиного європейського транспортного простору: тенденції розвитку, бар’єри та шляхи їх подолання - Бойченко, М.В.; Бояркін, М.О.; Осадчий, О.О. (Вісник економічної науки України, 2025)
У статті обґрунтовано стратегічне значення у відновленні економіки України процесу інтеграції автомобільного сегменту ринку вантажних перевезень в єдиний європейський транспортний простір. Визначено основні проблеми сучасного розвитку цього сегменту, пов’язані з геополітичними процесами. Наведено перелік бар’єрів інтеграційного процесу що виникають як внаслідок внутрішньоукраїнських проблем так і з боку транспортної системи Європейського Союзу. Сформовано комплекс заходів для подолання бар’єрів в процесі інтеграції автотранспортних перевезень вантажів України в єдиний транспортний простір ЄС. The article substantiates the strategic importance of the process of integrating the automobile segment of the freight market into the single European transport space in the recovery of the Ukrainian economy. A quantitative analysis of global, European and domestic freight transportation, including road transport, is provided. Key trends in the development of the international and, in particular, the European freight market are identified, which include the growth of demand for “green transport” and transparent environmental standards, intensive digitalization and automation, the transition to multimodality, as well as more stringent regulatory requirements and challenges in terms of staffing. A list of barriers to the integration process is provided, including Ukraine’s internal problems, such as the need to modernize infrastructure, imperfect legal and institutional capacity, competition in the market, as well as difficulties with compliance with regulatory requirements and interinstitutional coordination. On the EU side, the main barriers are infrastructure, regulatory, investment challenges and environmental sustainability issues. A set of measures has been formed to overcome barriers in the process of integrating Ukrainian road freight transport into the EU single transport space. In particular, it is important for Ukraine to finance infrastructure modernization, adapt legislation to European standards, stimulate competition, support small and medium-sized enterprises, ensure monitoring of regulations and strengthen inter-institutional coordination. On the EU side, important measures are joint cross-border infrastructure projects, harmonization of standards, conclusion of agreements to simplify customs and border procedures, attraction of investments through international funds, as well as the introduction of environmental standards and incentives for “green” transport.